2020
DOI: 10.1042/bsr20192589
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk effectors involved in neonatal hypoglycemia occurrence

Abstract: Hypoglycemia is a common metabolic condition in neonatal period, but severe and persistent hypoglycemia can cause neurological damage and brain injury. The aim of the present study was to analyze the risk factors of neonatal hypoglycemia in clinic. A total of 135 neonatal hypoglycemia infants and 135 healthy infants were included in the present study. The differences in birth weight between neonatal hypoglycemia group and healthy control group were analyzed via t test. The associations between neonatal blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…There are numerous studies indicating an association between hyperglycemia and/or GDM status and infant hypoglycemia (28,36). Our study observed that higher mean levels of pGCD59, HbA 1c , fasting glucose, 1-hour and 2-hour glucose levels, and GDM status (OGTT < 20 weeks of gestation) were statistically significantly associated with higher rates of NH.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…There are numerous studies indicating an association between hyperglycemia and/or GDM status and infant hypoglycemia (28,36). Our study observed that higher mean levels of pGCD59, HbA 1c , fasting glucose, 1-hour and 2-hour glucose levels, and GDM status (OGTT < 20 weeks of gestation) were statistically significantly associated with higher rates of NH.…”
Section: Discussionsupporting
confidence: 58%
“…Zhao et al (28) found that birth weight, poor feeding, and mother's GDM status are statistically significantly associated with NH. Doctor et al (29) found that SGA infants are 5 times more likely to develop hypoglycemia compared to AGA infants.…”
Section: Discussionmentioning
confidence: 99%
“…Se encontraron algunas similitudes con los resultados de la investigación de Singh et al donde se encontró como características neonatales más frecuentes: grande para la edad gestacional 25,9 %, sexo masculino 54,7 % (15) . En el estudio realizado por Zhao las características más frecuentes fueron sexo masculino 53,7 %, peso adecuado para la edad gestacional 78 %, recibieron lactancia materna precoz 88,8 % (16) Otras características neonatales como prematuridad, grande para la edad gestacional, otras complicaciones neonatales (RCIU, asfixia, sepsis, policitemia, taquipnea transitoria del recién nacido, síndrome de aspiración meconial) se relacionan con las características maternas, debido a que el neonato depende de la madre para su desarrollo y supervivencia. Un claro ejemplo es el caso del recién nacido grande para la edad gestacional, el cual resulta de altas concentraciones de glucosa materna durante el periodo gestacional, complicando así el trabajo de parto eutócico y favoreciendo algunas repercusiones en el recién nacido durante el parto, como prematuridad, asfixia, taquipnea, sepsis, etc.…”
Section: Discussionunclassified
“…Prolonged neonatal hypoglycemia has been associated with mental retardation, neurological deficits and recurrent seizures. [ 3 ] Some studies have shown perinatal hypoxia, small for gestational age and maternal hypertension to be factors associated with hypoglycemia in preterm newborns [ 4 , 5 ]. However, the exact mechanisms behind the observed negative effects are yet to be identified by neonatologists/endocrinologists to date.…”
Section: Introductionmentioning
confidence: 99%